Pemertahanan Kalangan Generasi Z : Antara Identitas dan Globalisasi dalam Bahasa Indonesia - Izza Afkarina Ulinnuha; Muhammad Hasbullah Ridwan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores how Generation Z maintains the use of the Indonesian language amid the challenges of globalization. In a modern era heavily influenced by foreign cultures and rapid digital development, a shift in language usage patterns among youth is becoming increasingly apparent. Foreign languages, particularly English, are frequently adopted in daily communication, which may threaten the role of the Indonesian language as a marker of national identity. The purpose of this research is to identify the factors that influence Generation Z’s language attitudes and practices, and to examine how they perceive Indonesian as part of their identity. Using a qualitative approach through interviews and observations, the findings reveal that although there is a tendency toward mixed language usage, there remains a level of awareness among Generation Z about the importance of preserving the Indonesian language. However, globalization and the dominance of foreign media content are significant influences shaping their linguistic habits. Therefore, strategic and youth-oriented efforts are needed to ensure that the Indonesian language remains relevant and valued in the future.